Enantioselective Pd‐Catalyzed Allylic Substitution using Phosphite‐Oxazoline PHOX‐Based Ligands containing a Methylene Linker. Issue 10 (15th March 2022) - de la Cruz‐Sánchez, Pol; Biosca, Maria; Magre, Marc; Faiges, Jorge; Margalef, Jéssica; Pàmies, Oscar; Diéguez, Montserrat
Abstract: High enantioselectivities (up to 99 %) and activities (TOF's up to >4000 h −1 ) are accomplished in the Pd‐catalyzed allylic substitution of a wide range of substrate types and nucleophiles using a family of phosphite‐oxazoline ligands. These ligands were derived from the PHOX ligand by exchanging the phosphine moieties by biaryl phosphites and a methylene spacer was introduced between the oxazoline and the phenyl ring. The wide substrate scope is due to the ability of the ligand family to adapt their ligand parameters to the reacting substrate. This ability also explains its high performance in other type of catalytic processes. Abstract : A family of phosphite‐oxazoline ligands derived from the PHOX provides high enantioselectivities (up to 99 %) and activities (TOF's up to >4000 h −1 ) in the Pd‐catalyzed allylic substitutions of a collection of substrates and nucleophiles. Its modularity is crucial to create a suitable chiral cavity for each substrate, which has been evidenced by DFT and experimental studies of the key Pd‐intermediates.